2018
DOI: 10.1186/s13045-018-0673-6
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAs in hematological malignancies: translating basic techniques into diagnostic and therapeutic strategies

Abstract: Recent studies have revealed that non-coding regions comprise the vast majority of the human genome and long non-coding RNAs (lncRNAs) are a diverse class of non-coding RNAs that has been implicated in a variety of biological processes. Abnormal expression of lncRNAs has also been linked to different human diseases including cancers, yet the regulatory mechanisms and functional effects of lncRNAs are still ambiguous, and the molecular details also need to be confirmed. Unlike protein-coding gene, it is much mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 189 publications
0
19
0
Order By: Relevance
“…This is of particular importance, because miRNAs lack an exclusive link to one target gene or disease and thus lack the high specificity, which is a requested feature of biomarkers [72,84]. Future studies should also include further investigations on the role of long noncoding RNAs in imatinib resistance as studies indicate that imatinib resistance can be modulated by long-non coding RNAs which target miRNAs thereby changing the expression of target associated with drug resistance like ABCB1 or ABCC2 [85][86][87].…”
Section: Discussionmentioning
confidence: 99%
“…This is of particular importance, because miRNAs lack an exclusive link to one target gene or disease and thus lack the high specificity, which is a requested feature of biomarkers [72,84]. Future studies should also include further investigations on the role of long noncoding RNAs in imatinib resistance as studies indicate that imatinib resistance can be modulated by long-non coding RNAs which target miRNAs thereby changing the expression of target associated with drug resistance like ABCB1 or ABCC2 [85][86][87].…”
Section: Discussionmentioning
confidence: 99%
“…57 In acute myeloid leukemia (AML), UCA1 promotes the proliferation of malignant cells by suppressing p27 kip1 . 14 Sedlarikova et al found that UCA1 was downregulated in MM patients, when compared to healthy donors. 58 Their results also revealed that higher levels of UCA1 were correlated to advanced ISS stage and 1q21 gain.…”
Section: Uca1mentioning
confidence: 99%
“…Metastasis‐associated lung adenocarcinoma transcript 1 (MALAT1), an 8.5‐Kb lncRNA (7 kb in mice) located on chromosome 11 (11q13.1), consists of two exons and is one of the few biologically well‐studied lncRNAs, and it has been reported to involve the regulation of gene expressions and the regulation of alternative splicing and cell cycle . MALAT1 misregulation has been shown to play a role in the development of several solid tumors, including lung, colorectal, bladder, and laryngeal cancers …”
Section: Mechanisms Of Lncrnas In MMmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanism of drug resistance to chemotherapeutic agents is not fully elucidated. Currently, more and more evidences have been proved that non-coding RNAs play critical roles in drug resistance [3][4][5][6]. ncRNAs including long non-coding RNAs (lncRNAs), microRNAs (miRNAs), circular RNAs (circRNAs), and PIWI-interacting RNAs (piRNAs) are suggested to be the potential promising therapeutic targets for overcoming drug resistance in the treatment of human cancers [7][8][9][10].…”
Section: To the Editormentioning
confidence: 99%